A Research on the effect of ICT Capability on the Society's Welfare: Multidimensional Deprivation Analysis including Technology as Attributes - Sangman Lee (International Telecommunications Society (ITS), 2018)
Nowadays, the concept of multidimensional poverty, inequality, deprivation, and well-being is not uncommon. While theoretical progress such as capability theory has provided rigorous framework for multidimensional analysis, empirical methods and tools such as UNDP's MPI (multidimensional poverty index) are rapidly growing. Apart from income, various attributes—e.g. health, educational attainment, crime rate of neighborhood, and so forth—are being included for measurement of society's deprivation level. This article attempt to use technology, especially ICT as one of main factors with South Korea's data. Specifically, by comparing deprivation between 5 years in Korea, it analyzes how ICT affects the overall welfare of society.
Keywords: 330; Multidimensional deprivation; ICT; Welfare economics; Poverty and Inequality